PIK3CA Gene Mutations in HNSCC - Cochicho, Daniela (2022)
Funding: This study was financially supported by the Virology Laboratory from the Pathology Department of the Portuguese Oncology Institute of Lisboa IUIC/1168, with contributions by the Research Center of the Portuguese Oncology Institute of Porto (project no. PI86-CI-IPOP-66-2017), by Base Funding-UIDB/00511/2020 of the Laboratory for Process Engineering, Environment, Biotechnology, and Energy—LEPABE—funded by national funds through the FCT/MCTES (PIDDAC), and Project 2SMART-engineered Smart materials for Smart citizens, with reference NORTE-01- 0145-FEDER-000054, supported by Norte Portugal Regional Operational Programme (NORTE 2020) under the PORTUGAL 2020 Partnership Agreement through the European Regional Development Fund (ERDF).